Does Internet Gaming Disorder Hinder Academic Performance? - Karnadi, Erwin Bramana; Pangestu, Stevanus (Jurnal Kajian Bimbingan dan Konseling, 2021)
In 2018, the WHO has categorized gaming disorder as an official disease. One of the ways to estimate a person’s gaming disorder level or status is to use the IGD-20 Test. The purpose of our research is to determine whether or not internet gaming disorder (IGD) has a significant negative impact on academic performance using binary dependent and two-staged least squares models. We obtained data from 390 Indonesian university students, consisting of their academic performance, IGD level, gaming behavior, and several of their economic and demographic characteristics. We found that 5.13 percent of the respondents have IGD. Using both probit and logit models, we also found that GPA has no significant impact on a person’s probability to have IGD. Finally, using a 2SLS model, we discovered that IGD has no considerable effect on GPA. Instead, income and gender are proven to be significant predictors of GPA.